Analisis Dan Desain Proses Bisnis Penanganan Perkara Hukum Menggunakan Konsep Vertikal Abstraksi Pada Lembaga Pengkajian Dan Konsultan Badan Hukum (LPKBH) Al-Baihaqy - Ahmad Baihaqy; Aditya Rachmadi; Nanang Yudi Setyawam (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
LPKBH Al-Baihaqy is one of the legal aid agencies in Indonesia located in Surabaya. From the interview result to LPKBH Al-Baihaqy Director, that client handling activity does not have Standard Operational Procedure (SOP) which become standard in carrying out case handling activity. This causes a problem of 6 out of 10 clients not consulting consultants, but the client directly contacts the lawyer LPKBH Al-Baihaqy. The ineffectiveness of each of the tasks and responsibilities as a whole led to a lot of misunderstandings in communication between clients, lawyers, consultants, and admins. So LPKBH Al-Baihaqy requires business process documentation to overcome these problems.This research aims to analyze and model the current business process (as-is) handling of legal cases on LPKBH Al-Baihaqy. The result of this research is modeling business process using BPMN standard. Modeling is done based on vertical analysis of abstraction, functional decomposition and RACI Chart mapping. The simulation of the business process model is done with all three levels: Process Validation, Time Analysis and Resource Analysis. The resulting modeling will be used as a SOP that can be recommended and agreed upon by all parties LPKBH Al-Baihaqy.